Exact Sciences' experience with the FDA and CMS parallel review program. (November 2015) - Ridge, John R; Statz, Sandra
Abstract : Colorectal cancer (CRC) is the third most commonly diagnosed cancer and the second leading cause of cancer death among men and women combined in the USA. Although the benefits of early CRC detection are widely recognized, screening rates are suboptimal. Cologuard ® is a multitarget stool DNA screening test that offers a unique non-invasive option for CRC screening. Cologuard was the first product to be reviewed under a pilot parallel review program jointly conducted by the US FDA and the Centers for Medicare & Medicaid Services (CMS). This parallel review process shortened the overall review for Cologuard and resulted in a preliminary National Coverage Determination that coincided with FDA approval.